2005
DOI: 10.1007/s00421-005-1351-2
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar and tibial bending stiffness as an index of bone strength in synchronized swimmers and gymnasts

Abstract: The purpose of this study is to compare a mechanical property of bone in world-class female athletes with different loading histories. Bone bending stiffness or EI (E is the modulus of elasticity and I, the moment of inertia) was measured noninvasively with the mechanical response tissue analyzer, that analyzes the response of bone to a vibratory stimulus. We evaluated the ulna, ulnar width, wrist density and tibia in 13 synchronized swimmers (SYN), eight gymnasts (GYM) and 16 untrained women (UNT) of similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…It is also important to note that these synchronized swimmers were eumenorrheic, which may represent a best-case scenario for bone stiffness in the sport. In the same study, bone-mineral density measured in the wrist was lower in the synchronized swimmers than either the gymnasts or untrained controls, which may point to a higher risk of osteoporosis (Liang et al, 2005). The lower bone-mineral density relative to gymnasts is likely related to the nature of the training being weight supported rather than load bearing.…”
Section: Bone Health and Menstrual Statusmentioning
confidence: 79%
See 2 more Smart Citations
“…It is also important to note that these synchronized swimmers were eumenorrheic, which may represent a best-case scenario for bone stiffness in the sport. In the same study, bone-mineral density measured in the wrist was lower in the synchronized swimmers than either the gymnasts or untrained controls, which may point to a higher risk of osteoporosis (Liang et al, 2005). The lower bone-mineral density relative to gymnasts is likely related to the nature of the training being weight supported rather than load bearing.…”
Section: Bone Health and Menstrual Statusmentioning
confidence: 79%
“…Overall it is a high-volume and high-intensity training program (Mountjoy, 2009), with the exception of periods devoted to choreography when much time may Scholarly reviewS be spent in the pool but with limited energy expenditure (Price & Carlsen, personal communication). Liang, Arnaud, Steele, Hatch, and Moreno (2005) found that the U.S. Olympic team trained 1,690 hr/ year, compared with around 1,000 for similar standard gymnasts. Unfortunately, they did not specify the gymnastics discipline.…”
Section: Training Patternsmentioning
confidence: 98%
See 1 more Smart Citation
“…Elite gymnastics is associated with marked improvements in bone density [1] and bone strength [2,3] that may be retained at least partly later in life [1,4,5]. The skeletal gains tend to be larger in the upper body [2] due to the unique pattern of loading induced by gymnastic maneuvers on the upper limbs, including weight-bearing and large muscular forces.…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of osteopenia in athletes is estimated at between 22 and 50% and that of osteoporosis at 13% (Khan et al, 2002). Studies done by Roby et al (1988) and Liang et al (2005) demonstrated lower BMD in the wrists of synchronized swimmers compared with gymnasts and untrained control subjects. Similar results were found for lower limb and lumbar measurements (Tanaka et al, 2006).…”
Section: Relative Energy Deficiency In Sportmentioning
confidence: 99%